2010
DOI: 10.1007/bf03337736
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a dynamic balance training protocol on podalic support in older women. Pilot Study

Abstract: The increased support surface and equal redistribution of body weight on both feet obtained in response to our training protocol may be postural adaptations sufficient to improve static balance in elderly women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 28 publications
3
24
0
Order By: Relevance
“…For some years now, theories of intellectual disabilities have been taking an approach centered on a more complete description of development in individuals with ID, known as “the whole-child approach”,1 in which emphasis is placed on all the factors that characterize atypical development. In line with this perspective, there is good agreement among theorists that sport and leisure can play a crucial role in promoting well-being and social integration among children and adolescents with intellectual or functional disabilities2,3 and in elderly people 4,5. Recent studies support the hypothesis that regular physical activity is associated with improved reaction time6 and better working memory in children with ID 7.…”
Section: Introductionmentioning
confidence: 86%
“…For some years now, theories of intellectual disabilities have been taking an approach centered on a more complete description of development in individuals with ID, known as “the whole-child approach”,1 in which emphasis is placed on all the factors that characterize atypical development. In line with this perspective, there is good agreement among theorists that sport and leisure can play a crucial role in promoting well-being and social integration among children and adolescents with intellectual or functional disabilities2,3 and in elderly people 4,5. Recent studies support the hypothesis that regular physical activity is associated with improved reaction time6 and better working memory in children with ID 7.…”
Section: Introductionmentioning
confidence: 86%
“…In this approach, health is not conceived as the absence of illness, but rather it involves, more globally, all the factors that lead to increasing well-being, such as physical activity. A variety of studies underlie the widespread consensus concerning the positive effects of motor activity on mental and physical health from childhood to senescence 24…”
Section: Introductionmentioning
confidence: 99%
“…Elderly people generally assume the sitting position for a longer period of time,5 maintaining prolonged lumbar flexion. Several studies have demonstrated that exercise programs can improve body balance,6,7 bodyweight distribution on the feet,8 muscle strength, flexibility,9 and QOL10 in the elderly.…”
Section: Introductionmentioning
confidence: 99%